The Thiol Reductase Activity of YUCCA6 Mediates Delayed Leaf Senescence by Regulating Genes Involved in Auxin Redistribution - Cha, Joon-Yung; Kim, Mi R.; Jung, In J.; Kang, Sun B.; Park, Hee J.; Kim, Min G.; Yun, Dae-Jin; Kim, Woe-Yeon (Frontiers in Plant Science, 2016)
Auxin, a phytohormone that affects almost every aspect of plant growth and development, is biosynthesized from tryptophan via the tryptamine, indole-3-acetamide, indole-3-pyruvic acid, and indole-3-acetaldoxime pathways. YUCCAs (YUCs), flavin monooxygenase enzymes, catalyze the conversion of indole-3-pyruvic acid (IPA) to the auxin (indole acetic acid). Arabidopsis thaliana YUC6 also exhibits thiol-reductase and chaperone activity in vitro; these activities require the highly conserved Cys-85 and are essential for scavenging of toxic reactive oxygen species (ROS) in the drought tolerance response. Here, we examined whether the YUC6 thiol reductase activity also participates in the delay in senescence observed in YUC6-overexpressing (YUC6-OX) plants. YUC6 overexpression delays leaf senescence in natural and dark-induced senescence conditions by reducing the expression of SENESCENCE-ASSOCIATED GENE 12 (SAG12). ROS accumulation normally occurs during senescence, but was not observed in the leaves of YUC6-OX plants; however, ROS accumulation was observed in YUC6-OXC85S plants, which overexpress a mutant YUC6 that lacks thiol reductase activity. We also found that YUC6-OX plants, but not YUC6-OXC85S plants, show upregulation of three genes encoding NADPH-dependent thioredoxin reductases (NTRA, NTRB, and NTRC), and GAMMA-GLUTAMYLCYSTEINE SYNTHETASE 1 (GSH1), encoding an enzyme involved in redox signaling. We further determined that excess ROS accumulation caused by methyl viologen treatment or decreased glutathione levels caused by buthionine sulfoximine treatment can decrease the levels of auxin eﬄux proteins such as PIN2-4. The expression of PINs is also reduced in YUC6-OX plants. These findings suggest that the thiol reductase activity of YUC6 may play an essential role in delaying senescence via the activation of genes involved in redox signaling and auxin availability.